Children and childhood in the Ottoman Empire (Edinburgh)
xxii, 408 sayfa
Keywords: “How did adults, religious institutions and the state view children during the Ottoman Empire? This volume gathers specialists in the social history of the Ottoman Empire as a whole - in regions ranging from Anatolia through the Arab provinces to the Balkans, and from the 15th to the early 20th century - to respond to recent theoretical calls to recognise children as active agents in history. Divided into five thematic sections (concepts of childhood, family interrelationships, children outside family circles, children's bodies, and education), the volume covers the social and political structure of the Ottoman Empire. It uses the innovative prism of children as social agents who are not only shaped by but also shape society, rather than being the passive recipients of their social environment.” --